Technical considerations towards commercialization of porcine respiratory and reproductive syndrome (PRRS) virus resistant pigs - A. Mark Cigan; Pieter W. Knap (CABI Agriculture and Bioscience)
Abstract The selection and introduction of disease resistance genes in livestock not only provide health benefits to animals but opportunities for breeders and farmers to meet the growing demand for high-quality meat and milk while reducing agriculture’s footprint on the environment. As traditional methods of classical breeding and selection for trait improvement are slow, recent progress in several areas of biology including (a) understanding host–pathogen interactions, (b) inexpensive and rapid DNA sequencing, and (c) robust gene editing like CRISPR-Cas provide geneticists tools to accelerate discovery and deployment of disease resistance alleles in livestock. Using these advances, the introduction of resistance genes into commercially relevant germplasm requires access to genetically superior livestock, an infrastructure for scalable allele deployment, freedom to operate, global regulatory approvals, and acceptance of gene edited livestock by producers and consumers. Importantly, academic researchers have recently discovered that modification of the CD163 gene in pigs can confer resistance to the virus that causes porcine reproductive and respiratory syndrome (PRRS). While this achievement represents a major step towards solving an important disease in livestock, to realize the positive impact on animal health while benefiting the pork industry and consumers, it is necessary to introduce this recessive disease resistance allele into commercial breeding populations. Rather than backcrossing the resistance gene from a few non-commercial founders, as a global supplier of high genetic merit livestock genetics, Genus plc and its pig division PIC (Pig Improvement Company) with Genus R&D have mobilized advances in reproductive biology, gene editing, DNA sequencing, and bioinformatics to simultaneously generate and introduce a single modified CD163 allele across four genetically diverse porcine lines of commercial importance that prevents PRRS virus (PRRSV) infection. This report focuses on technical aspects for a scaled gene editing program to consider for rapid and efficient generation and advancement of a small population of non-transgenic founder pigs for commercial breeding. This high genetic merit herd containing a PRRS disease resistance allele will provide important benefits to animal health and food chain value once approved for commercial sale and export.